Cumingianoside A, a Phyto-Triterpenoid Saponin Inhibits Acquired BRAF Inhibitor Resistant Melanoma Growth via Programmed Cell Death - Cvetanova, Biljana; Shen, Ya-Ching; Shyur, Lie-Fen (Frontiers in Pharmacology, 2019)
Mutated proto-oncogene BRAF is a bona fide therapeutic target for melanomas. Regrettably, melanoma acquires resistance to BRAF inhibitors, e.g., vemurafenib (PLX4032) casting doubt on this promising melanoma targeted therapy. In this study, we explored the bioactivity of triterpenoid saponin cumingianoside A (CUMA), isolated from leaves and twigs of Dysoxylum cumingianum against PLX4032-resistant BRAFV600E mutant melanoma A375-R in vitro and in vivo. Our data show that CUMA treatment inhibited A375-R melanoma cell proliferation in a time- and dose-dependent manner. CUMA also suppressed the activity of CDK1/cyclin B1 complex and led to G2/M-phase arrest of A375-R cells. Furthermore, CUMA treatment resulted in induction of apoptosis as shown by the increased activation of caspase 3 and caspase 7, and the proteolytic cleavage of poly(ADP-ribose) polymerase (PARP). We also observed that CUMA induced autophagy-like activity in A375-R cells, as shown by the increased expression of autophagy-related genes and increased formation of autophagosomes. Moreover, we found that CUMA treatment induced ER stress response and co-treatment with an ER stress inhibitor (4-PBA) could attenuate apoptosis induced by CUMA. Importantly, orally administered CUMA as a single agent or in combination with PLX4032 exhibited strong tumor growth inhibition in a PLX4032-resistant A375-R xenograft mouse model, and with little toxicity. This is the first report to explore the anti-tumor activity of CUMA in vitro and in vivo mechanistically, and our results imply that this triterpenoid saponin may be suitable for development into an anti-melanoma agent.